The association of sport performance with ACE and ACTN3 genetic polymorphisms: a systematic review and meta-analysis. - Fang Ma; Yu Yang; Xiangwei Li; Feng Zhou; Cong Gao; Mufei Li; Lei Gao (PLoS ONE)
Background Genetic polymorphism is suggested to be associated with human physical performance. The angiotensin I-converting enzyme insertion/deletion (ACE I/D) polymorphism and the α-actinin-3 gene (ACTN3) R577X polymorphism have been most widely studied for such association analysis. However, the findings are frequently heterogeneous. We aim to summarize the associations of ACE I/D and ACTN3 R577X with sport performance by means of meta-analysis. Methods We systematically reviewed and quantitatively summarized published studies, until October 31, 2012, on relationship between ACE/ACTN3 genetic polymorphisms and sports performance, respectively. Results A total of 366 articles on ACE and 88 articles on ACTN3 were achieved by literature search. A significant association was found for ACE II genotype compared to D allele carriage (DD+ID) with increased possibility of physical performance (OR, 1.23; 95% CI, 1.05-1.45). With respect to sport discipline, the II genotype was found to be associated with performance in endurance athletes (OR, 1.35; 95% CI, 1.17-1.55). On the other hand, no significant association was observed for ACTN3 RR genotype as compared to X allele carriage (XX+RX) (OR, 1.03; 95% CI, 0.92-1.15). However, when restricted the analyses to power events, a significant association was observed (OR, 1.21; 95% CI, 1.03-1.42). Conclusion Our results provide more solid evidence for the associations between ACE II genotype and endurance events and between ACTN3 R allele and power events. The findings suggest that the genetic profiles might influence human physical performance.